Fabrication of Microfibrous and Nano-/Microfibrous Scaffolds: Melt and Hybrid Electrospinning and Surface Modification of Poly(L-lactic acid) with Plasticizer. (5th December 2013) - Yoon, Young Il; Park, Ko Eun; Lee, Seung Jin; Park, Won Ho
Abstract : Biodegradable poly(L-lactic acid) (PLA) fibrous scaffolds were prepared by electrospinning from a PLA melt containing poly(ethylene glycol) (PEG) as a plasticizer to obtain thinner fibers. The effects of PEG on the melt electrospinning of PLA were examined in terms of the melt viscosity and fiber diameter. Among the parameters, the content of PEG had a more significant effect on the average fiber diameter and its distribution than those of the spinning temperature. Furthermore, nano-/microfibrous silk fibroin (SF)/PLA and PLA/PLA composite scaffolds were fabricated by hybrid electrospinning, which involved a combination of solution electrospinning and melt electrospinning. The SF/PLA (20/80) scaffolds consisted of a randomly oriented structure of PLA microfibers (average fiber diameter = 8.9 µm) and SF nanofibers (average fiber diameter = 820 nm). The PLA nano-/microfiber (20/80) scaffolds were found to have similar pore parameters to the PLA microfiber scaffolds. The PLA scaffolds were treated with plasma in the presence of either oxygen or ammonia gas to modify the surface of the fibers. This approach of controlling the surface properties and diameter of fibers could be useful in the design and tailoring of novel scaffolds for tissue engineering.